Medical student exposure to cardiothoracic surgery in the United Kingdom. (15th March 2019) - Gasparini, Marisa; Jayakumar, Shruti; Ayton, Sarah; Nardini, Marco N; Dunning, Joel D
Abstract: OBJECTIVES: There has been declining interest in cardiothoracic surgery amongst medical graduates. This survey examines the exposure of British medical students to cardiothoracic surgery in various settings and its relationship with students' interest in the speciality. METHODS: A questionnaire composed of 14 quantitative and qualitative items was distributed amongst 162 medical students. The survey included questions on demographics, interest in cardiothoracic surgery, mechanisms of exposure to the speciality and desire to pursue a career in cardiothoracic surgery before and after exposure. RESULTS: Amongst the surveyed students, 71.0% reported exposure to cardiothoracic surgery as part of their medical school curricula and 24.7% reported extracurricular exposure. Of the students, 46.7% reported clinical exposure. Overall, 27.1% of students reported interest in a career in cardiothoracic surgery, which was higher amongst students who had curricular (29.6%), clinical (35.5%) or extracurricular exposure (50.0%). Amongst interested students, 43.2% engaged in extracurricular cardiothoracic activities compared with 16.1% of students not interested in pursuing the speciality. Confidence in career choice after exposure increased more in interested students (20.4%) than not interested students (1.6%). Students rated exposure and mentorship as the most important factor in promoting a career in cardiothoracic surgery. CONCLUSIONS: Medical students with an interest in cardiothoracic surgery are more likely to organize independent attachments in the speciality and attend extracurricular events; however, many students might fail to identify cardiothoracic surgery as an area of interest because of the lack of exposure at medical school.